Division and unity in the struggle: African politics on the Witwatersrand in the 1920s - Bonner, Philip (My University, 1992)
Accounts of African political organisation in South Africa between the 1920s and 1950s have tended to veer between two extremes – institutional studies of national political organisations and micro studies of local struggles in which the national political organisations played an intermittent and often inconspicuous part. The politics of specific regions of the country have as a result been poorly served. We have Bradford's study of the rural organisation of the Industrial and Commercial Workers' Union, and Lodge's accounts of two ANC campaigns in two key urban areas - the Defiance Campaign in the Eastern Cape and the Bantu Education boycott on the East Rand – but aside from these there is a notable dearth of such middle level exercises which might help bring national political organisation and local level struggles into a closer and more meaningful relationship to one another. Among the most conspicuous gaps in the literature are studies of the politics of the Witwatersrand and Eastern Cape. These two urban areas are usually depicted as the forcing houses of black politics, but neither has attracted the attention that it might have been expected to have received. On the Witwatersrand a number of fine local studies have been produced but none gives a broader sense of the pattern and movement of political activities on the Rand. A large part of the reason has been the sheer scale of the enterprise, but enough of the pieces have now been assembled for us to begin to compose the broader picture. This paper represents the first stage of such an attempt.
African Studies Seminar series. Paper presented 9 March, 1992. Not to be quoted without the author's permission.
Keywords: South Africa. Political history.; Political participation. South Africa. Witwatersrand; Witwatersrand (South Africa)